Unlocking the nexus: exploring the effect of urban green innovation on haze pollution and carbon emissions intensity in Chinese cities - Li, Wenlong; Wang, Chao; Duan, Dingkang; Li, Qiming; Tian, Rutao; Ma, Tianyu (Frontiers in Environmental Science, 2024)
As a comprehensive and systematic approach to innovation, green innovation has become an important tool for reducing haze and carbon intensity. We explore the influence of urban green innovation on haze pollution and carbon emissions intensity based on balanced panel data in China from 2012 to 2018. The results indicate the following: (1) The influence of green innovation on carbon emissions intensity and haze pollution exhibits a significant inverted U-shaped relationship. (2) We explore the mediating channels through which green innovation affects carbon emissions intensity and haze pollution. Specifically, the inverted U-shaped impacts of green innovation on energy intensity and resource dependence. (3) The inverted U-shaped relationship between green innovation and carbon emissions intensity holds for both resource-based and non-resource-based cities. (4) The U-shaped relationships, whether regarding carbon emissions intensity or haze pollution, are only applicable to non-environmental priority cities. By incorporating green innovation into the framework of coordinated carbon-haze governance, this paper offers valuable insights for the formulation of more effective environmental management measures by governments.